Nitric oxide activation and reduction by heme-copper oxidoreductases and nitric oxide reductase - Pinakoulaki, Eftychia; Varotsis, Constantinos (My University, 2008)
The understanding of the dynamics and conformational control involved in the interplay between structure and function of nitric oxide reductase (Nor) and heme-copper oxidoreductases in their function to convert nitric oxide (NO) to nitrous oxide (N2O) is of fundamental importance in bioenergetics. We have applied resonance Raman spectroscopy to investigate the NO ligation/deligation reactions and the extent of communication between the metal centers at the heme a3-CuB site of heme-copper oxidases and of the heme Fe-non-heme Fe in Nor. The present study provides information of the electronic and vibrational structure of intermediates, and thus, it forms the basis for an atomic-level description of the key steps in the N-N bond formation and the N-O bond cleavage mechanism. The present experiments provide evidence as to the validity of the proposed hypothesis of the common evolutionary origin of aerobic respiration and bacterial denitrification
Keywords: Nitric oxide; Bacteria; Copper; Cytochrome b; Iron ions; Oxidoreductases; Denitrification